2022
DOI: 10.1021/jacs.2c11806
|View full text |Cite
|
Sign up to set email alerts
|

A Semicrystalline Furanic Polyamide Made from Renewable Feedstocks

Abstract: Semi-aromatic polyamides (SAPs) synthesized from petrochemical diacids and diamines are high-performance polymers that often derive their desirable properties from a high degree of crystallinity. Attempts to develop partially renewable SAPs by replacing petrochemical diacids with biobased furan-2,5-dicarboxylic acid (FDCA) have resulted in amorphous materials or polymers with low melting temperatures. Herein, we report the development of poly(5-aminomethyl-2-furoic acid) (PAMF), a semicrystalline SAP synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…These peaks are associated to the polyester unit as evidenced, for example, in the poly­(1,6-hexylene 2,5-furandicarboxylate) XRD pattern, published elsewhere , and also in this work (Figure S5 of the Supporting Information). The diffractograms of the PEA incorporating higher amount of amide units (PEAF 3–4 ) display the main diffraction reflections peaks observed in the PEAF 1–2 patterns, at 2θ ∼17 and 24°, as well as several new sharp ones at 2θ ∼8, 9, 10, 12, 15, 22, and 30°, previously detected in furan-based polyamides, and these may arise from the establishment of a crystalline arrangement where the amide group, probably involved in intermolecular hydrogen bonds, plays a fundamental role. The degree of crystallinity ( X c ) values (Table ) clearly demonstrate the high crystallinity of these novel PEAFs, despite the fact that purely polyamide (PAF) was found to be an essentially amorphous displaying only a halo centered at 17° (Figure S6 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 82%
“…These peaks are associated to the polyester unit as evidenced, for example, in the poly­(1,6-hexylene 2,5-furandicarboxylate) XRD pattern, published elsewhere , and also in this work (Figure S5 of the Supporting Information). The diffractograms of the PEA incorporating higher amount of amide units (PEAF 3–4 ) display the main diffraction reflections peaks observed in the PEAF 1–2 patterns, at 2θ ∼17 and 24°, as well as several new sharp ones at 2θ ∼8, 9, 10, 12, 15, 22, and 30°, previously detected in furan-based polyamides, and these may arise from the establishment of a crystalline arrangement where the amide group, probably involved in intermolecular hydrogen bonds, plays a fundamental role. The degree of crystallinity ( X c ) values (Table ) clearly demonstrate the high crystallinity of these novel PEAFs, despite the fact that purely polyamide (PAF) was found to be an essentially amorphous displaying only a halo centered at 17° (Figure S6 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 82%
“…It is reported that the furan ring facilitates the formation of intramolecular hydrogen bonds between the amide hydrogen atoms and oxygen atoms of the furan ring, thereby reducing the interchain hydrogen bonding interactions that are considered vital for the crystallization. 9,26 As shown in Fig. 4b, the glass transition temperature (T g ) decreases as the carbon chain length of the aliphatic segment in the diamine increases.…”
Section: Synthesis Of Furan-based Polyamidesmentioning
confidence: 78%
“…The molecular weights, thermal properties, and stability of the synthesized FPAs are comparable to those of their petrochemical counterparts. 9,10 This suggests that the FPAs have great potential to serve as bio-based replacements for traditional petroleum-based polyamides.…”
Section: Synthesis Of Furan-based Polyamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…5‐Formyl‐2‐furancarboxylic acid (FFCA) is one of intermediates in the successive oxidation of HMF into FDCA, [4] and its reductive amination can provide access to 5‐aminomethyl‐2‐furancarboxylic acid (AMFC), a furan‐containing amino acid [5] . Recently, Kanan and co‐workers reported a promising semicrystalline furanic polyamide material synthesized by AMFC polycondensation, [6] which has glass‐transition and melting temperatures comparable to that of commercial materials and higher than that of furanic semi‐aromatic polyamides ever reported. In addition, this chemical and derivatives could be used to produce furan‐based cyclic oligopeptides, [7] which are capable of selectively inhibiting the activity of telomerase, making them promising ligands for exploration for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%